The effectiveness of formal mentoring programs into performance of employee in the small, medium and enterprise company (manufacturing) in Kuantan - Nurul Amiera , Yahya (2014)
This study is explored the effectiveness of formal mentoring programme into performance of employee in the Small, Medium and Enterprise manufacturing company (SME) in Kuantan. The objective of this study is to identify roles and responsibilities of mentor, mentee and organisational to improve employee performance, to evaluate the effectiveness of staff mentoring programs into employee performance and to investigate a formal mentoring programs in organization to managing employee performance. Poor performance can be defined as a failure by an employee to achieve and sustain a satisfactory standard in their job with their skill, knowledge and capability. Employer must to implement a suitable program to improve and managing performance of employee such as mentoring program. Employee performance can be affected by mentoring program. To answers the question contained in this study, the methods used is questionnaire. Statistics respondents consist of employee, supervisor and human resources manager. This study used a quantitative research design and instrument of this study. This study is using the Statistical Package for Social Science (SPSS) to analyse data collected. As a sampling, it is used at random. There are 56 individuals responded to the questionnaire items were distributed. The findings from this study indicate that mentoring program is one of the programs that give a positive impact to the employee performance because performance of employee was increased after the employer was implementing the program